2007
DOI: 10.1111/j.1365-2923.2007.02801.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between assessment results and approaches to learning and studying in Year Two medical students

Abstract: The correlations met our expectations in terms of direction, but were weaker and less consistent than anticipated. Possible reasons include the drive to test basic (core) material, the use of questions that may limit students' scope of expression and markers' ability to detect a deep approach. It is, however, important to refine medical programmes, particularly assessments, so that they concur with and do not adversely affect students' learning approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 16 publications
6
86
1
4
Order By: Relevance
“…The use of these assessment methods in the curriculum of medical education has promoted an integrated approach to learning anatomy. Several studies showed that this integrated approach improves student participation and understanding [20,21].…”
Section: Introducing Clinical Reasoning Into the Teaching Of Anatomymentioning
confidence: 99%
“…The use of these assessment methods in the curriculum of medical education has promoted an integrated approach to learning anatomy. Several studies showed that this integrated approach improves student participation and understanding [20,21].…”
Section: Introducing Clinical Reasoning Into the Teaching Of Anatomymentioning
confidence: 99%
“…12 The intended characteristics are in terms of the viewpoint of the learning process as the basis for the emergence of an active or passive attitude to learn. 13,14 In this study, the initiative to do adequate preparation for learning was a form of active attitude, while the inadequate preparation for learning was considered a passive attitude that led the students to learn for granted. Students' who have adequate preparation of their learning strategies have the character of 'deep approach learning', whereas students with inadequate preparation of their learning strategies have the character of 'surface approach learning'.…”
Section: Discussionmentioning
confidence: 99%
“…If the purpose of the learning process is understanding, then deep approach learning is a better than the surface approach. [13][14][15][16] Therefore, in clinical learning, the implementation of learning strategies should be done with adequate preparation rather than inadequate preparation. However, this study found a higher tendency of the students towards the learning strategies with inadequate preparation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that this integrated approach improves student participation and understanding. 20,21 Our analysis may have some limitations. Indeed, it reflects only reflections on the faculty of medicine of Saint-Louis.…”
Section: Introducing Clinical Reasoning Into the Teaching Of Anatomymentioning
confidence: 99%